2018
DOI: 10.1002/anie.201711606
|View full text |Cite
|
Sign up to set email alerts
|

Precisely Tailoring Upconversion Dynamics via Energy Migration in Core–Shell Nanostructures

Abstract: Upconversion emission dynamics have long been believed to be determined by the activator and its interaction with neighboring sensitizers. Herein this assumption is, however, shown to be invalid for nanostructures. We demonstrate that excitation energy migration greatly affects upconversion emission dynamics. “Dopant ions’ spatial separation” nanostructures are designed as model systems and the intimate link between the random nature of energy migration and upconversion emission time behavior is unraveled by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
97
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 58 publications
(7 reference statements)
8
97
0
Order By: Relevance
“…From 2012 up to now, the gadolinium network‐mediated energy migration strategy has been reported with slight modifications mainly focused on the chemical nature of doping elements and their relative organization in multishell architectures 5h,9,23. CSX upconverting structures have been used for multicolor emission modulated by laser power, full‐color tuning through nonsteady‐state UC, orthogonal excitations–emissions UC, and lifetime regulation …”
Section: Core–shell Upconverting Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2012 up to now, the gadolinium network‐mediated energy migration strategy has been reported with slight modifications mainly focused on the chemical nature of doping elements and their relative organization in multishell architectures 5h,9,23. CSX upconverting structures have been used for multicolor emission modulated by laser power, full‐color tuning through nonsteady‐state UC, orthogonal excitations–emissions UC, and lifetime regulation …”
Section: Core–shell Upconverting Architecturesmentioning
confidence: 99%
“…In addition to the size of the starting seeds and shells, other parameters were found to influence the amount of intermixing, such as the shell growth methods (Figure , panel B). Therefore, although in specific cases the interfaces can be fairly abrupt, intermixing is a general observation in upconverting NCs, and will be important to further engineer energy transport properties 27c. Continued efforts are still required to precisely relate structures to growth conditions and it should be noted that additional parameters not yet identified could influence the formation and characteristics of interfaces as well.…”
Section: Quantitative Chemical Analysis Of Core–shell Structuresmentioning
confidence: 99%
“…[3] Although the LRET of UCNPs has been extensively applied in biosensing and biomedicine,the low energy transfer efficiency due to the relatively low extinction coefficients of lanthanide dopants [4] and the constraint in nanoparticle dimension [5] of UCNPs is still abottleneck to further applications.Several multilayer UCNPs have been proposed to enhance the transfer efficiency. [6][7][8][9][10] However,a ssembling as pacer layer [7] or an inert shell [8] on UCNPs increases the distance from the emitter to the surface LRET acceptor,while some approaches to reduce particle size [9] increase surface quenching and lower the quantum yield. [1b] To overcome the distance effect, at hin shell of NaYbF 4 :Tm has been constructed on UCNPs for confining energy in the shell to enhance the upconversion luminescence.…”
mentioning
confidence: 99%
“…Several multilayer UCNPs have been proposed to enhance the transfer efficiency. [6][7][8][9][10] However,a ssembling as pacer layer [7] or an inert shell [8] on UCNPs increases the distance from the emitter to the surface LRET acceptor,while some approaches to reduce particle size [9] increase surface quenching and lower the quantum yield. [1b] To overcome the distance effect, at hin shell of NaYbF 4 :Tm has been constructed on UCNPs for confining energy in the shell to enhance the upconversion luminescence.…”
mentioning
confidence: 99%
“…On the other hand, confining the energy migration within a narrow layer or a small localized structure can improve the upconversion in a sensitizer‐activator system by minimizing the excitation energy loss . Just recently, it is found that the energy migration can be used to tune the luminescence dynamics of lanthanides in a nanostructure, resulting in a wide distribution of the decay time …”
mentioning
confidence: 99%